Fijian bats : interactions between people and bats and a preliminary investigation into zoonotic pathogens : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Veterinary Science in Wildlife and Zoo Animal Health at Massey University, Palmerston North, Manawatū, New Zealand - McCutchan, Jessica Louise (Massey University, 2021)
Conservation is an increasingly important global crisis, especially for the conservation of keystone species such as bats. In Fiji, five of the six species of bats are considered threatened to critically endangered on the ICUN Red List. Human encroachment in wild places and habitat loss, are invariably leading to increased contact between people and wildlife. Interactions between humans and bats can be both beneficial and detrimental to each species. This pilot study was undertaken to identify and quantify these interactions in Fiji and recognise the Fijian people’s perception of bats. People were interviewed across the three main islands of Fiji; Viti Levu, Vanua Levu and Taveuni. Throughout these islands, bats were generally perceived as positive. The majority of participants consume and come into contact with bats, or with their urine, faeces, blood and saliva. Young adults and men are more likely to come into contact with bats in Fiji than women. Quantifying these interactions and identifying other risk factors for bat exposure is an important step in targeting conservation efforts, community engagement and education. Through understanding these inter-species dynamics, at risk groups for possible zoonotic pathogen exposure have been identified. Education efforts towards bat conservation and public health risks can be more effectively developed when directed to at risk groups. This education material can build upon the positive perceptions surrounding bats and their importance in Fiji biodiversity. A survey was also carried out for selected zoonotic pathogens Leptospira sp., Histoplasma sp., coronaviruses and paramyxoviruses. Pooled urine and faecal samples were analysed for selected potentially zoonotic pathogens. We identified four genetically distinct Leptospira sp. in urine from Pteropus tonganus and samples collected at a Notopteris macdonaldi roost site. These findings contribute new information to the understanding of leptospirosis in Fiji, which is a nationally notifiable disease with a significant disease burden. Developed with a One Health focus, this pilot study provides baseline data for current disease status and up to date advice regarding public health information, guidelines and education.
Keywords: 300905 Veterinary epidemiology